IMPROVING THE COGNITIVE DEVELOPMENT OF 5-6 YEARS OLD CHILDREN THROUGH FLAG ICE CREAM STICK GAMES - Ahmad, Nazwa Aulia; Yulianty S, Nadya (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to improve the cognitive and language development of children aged 5–6 years through the use of ice cream stick flag games. The background of this study is the low ability of children to recognize basic counting concepts and express themselves in simple language during learning activities. The method used is classroom action research (CAR) conducted in two cycles. The research subjects consisted of 18 children in group B at a kindergarten. The data collection instrument was a child development observation sheet, which was analyzed using quantitative descriptive methods. The results of the study show an increase in children's cognitive and language development from the pre-cycle to cycle II. In the pre-cycle, there were 10 children (55%) who showed development, increasing in cycle I to 12 children (67%), and in cycle II increasing significantly to 15 children (80%). This proves that the ice cream stick flag game medium is able to provide a fun learning experience, motivate children to be active, and is effective in improving the cognitive and language development of early childhood. Thus, it can be concluded that the flag ice cream stick game can be used as a creative and interactive learning medium that supports children's development, particularly in the cognitive and language areas.